Torebka: płeć i codzienność = A handbag: gender and everyday life - Albański, Łukasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article proposes reconstruction of social contexts in which a handbag functions as an attribute of femininity. A handbag is an object which makes it possible to document everyday life of women, to look at their personal relationships, childhood memories, individual preferences. A handbag is perceived as an intimate world of women, the world to which access of others is limited. The contexts of meanings of a handbag, as presented in the article, are based on the material from open interviews. The article is descriptive and is meant to seize the experience of women with handbags in the overall social context.
Keywords: płeć; torebka; codzienność; gender; handbag; everyday practices